(untitled) (Academicia Globe: Inderscience Research, 2022)
This article discusses the aspects and existing problems of the organization of remote banking services provided by commercial banks to individuals. The analysis of the current state and prospects of development of remote banking services in commercial banks of Uzbekistan, as well as practical proposals for the expansion of remote banking services are presented.